Artur e Santiago: relações entre jornalismo narrativo e cinema-documentário - Silva, Suéllen Rodrigues Ramos da (2014)
This dissertation aims to examine the possible approximation between productions of narrative journalism and documentary film. We have used the profile Artur tem um problema (2010a), published in the piauí magazine, written by João Moreira Salles, as a starting point for examining the main objective of our research , the film Santiago: uma reflexão sobre o material bruto (2007), also written by Salles, establishing connections with other journalistic and filmic texts. Both in profile and in the documentary, we have verified the presence of intrinsic elements of narrative journalism (LIMA, 1995; WOLFE, 2005), which allows us to discuss the concept of cinematic literary journalism (LIMA, 2003). Through analysis, we have found out the convergence between these different fields of knowledge in narrative construction from the choice of a way of narrating grounded in experience (BENJAMIN, 1980; SANTIAGO, 1989), dialogue (MEDINA, 1986) and humanization of the character. Artur and Santiago do not only relate each other due to authorship. In both works, we have main characters who, to some extent, inhabit individual universe. In both, Salles plays not only as the narrator s identity (GENETTE, 1995; REIS, LOPES, 1988), but also as a character, quite different in degrees from a work to another, and attributes an essayistic style to the narratives (ADORNO, 2003a; LUKÁCS, 2008), bringing reflections on parallel themes: the profile (VILAS BOAS, 2003), the nature of mathematics; in the film the documentary itself as a genre itself (DA-RIN, 2004; NICHOLS, 2005; RAMOS, 2008). Santiago, however, introduces greater complexity and artistic dimension, allowing the deepening of discussion about form and language. A central question is to observe which gives an esthetical value (CHKLOVSKI, 1973; JAKOBSON, 1995; TODOROV, 1979), something that we try to understand by comparing it with the profile of the mathematician Artur Avila. For that, we have also considered its context of production, from the recording of the interview with Santiago Badariotti Merlo, former butler of Moreira Salles family, in 1992, to final montage, thirteen years later; the choices of the director to the narrative structure, the relation between documentarian and character (COUTINHO, 2013a; SALLES, 2005), besides other constituent elements of the work, as metafictionality and intonation (BAKHTIN, 2011).